The Effect of Transformational Leadership on Affective Commitments with Job Satisfaction and Organizational Culture as An Intervening Variable - Nurhayati Achmad Ratina; Ratna Indrawati Lestariani; Rhian Indradewa; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2020)
This study aims to examine the effect of Transformational Leadership on Job Satisfaction, Organizational Culture, and Affective Commitment. This study will raise the relationship between job satisfaction and affective commitment as a literature gap. The population used in this study over Harapan Mulia Hospital employees around 200 employees. Here, we use 34 question items with a minimum of 34 x 5 or 170 samples. The research design in this study is explanatory research that will prove the causal relationship between the independent variables and the dependent variable. Significant levels and interrelationships between variables were analysed using the structural equation model (SEM) method Testing with structural analysis Lisrel 8.80 and for descriptive analysis using Statistical Package for Social Science (SPSS) version 20.00. The results shows that the application of Transformational Leadership had a positive and significant effect on job satisfaction (T-Statistics = 6,16). These results are in line with several previous studies that explain the impact of transformational leadership on job satisfaction. Furthermore, that there is a positive and significant influence between Transformational Leadership on Organizational Culture (T-Statistics = 5,23), there is a positive and significant effect on Transformational Leadership on Affective Commitment (T-Statistics = 2,98), there is a significant influence between employee satisfaction on affective commitment (T-Statistics = 2,39), there is a significant relationship between organizational culture and affective commitment (T-Statistics = 2,68). This means that the higher application of a company's organizational culture will encourage employees to have a better affective commitment.